TRANSFORMER-BASED PHOTOVOLTAIC SYSTEM WITH CASCADED CONVERTERS WITH DISCONTINUOUS SYNCHRONIZED MODULATION - Oleschuk V.I.; Sizov A.S. (Problems of the Regional Energetics, 2011)
The paper presents results of analysis of operation of photovoltaic system on the base of dual inverters with discontinuous synchronized pulsewidth modulation (PWM). Two basic schemes of discontinuous synchronized PWM, applied for control of dual-inverter system under different operation conditions, have been analyzed and compared.